Anticancer selectivity of Momordica charantia L. Seeds Extract and Column Fraction on Raji , HeLa and T47D Cell Lines - Hersri Rochmad Parhardian Hersri Rochmad Parhardian (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Momordica charantia L. has been used traditionally as medicinal plant in Indonesia. The seed extracts have active substances in the form of ribosome-inactivating proteins (RIPsï€´. Almost all RIPs can eliminate virus infection and kill cancer cells. Some cancer cells like Raji cell line and HeLa cell line are derived from Burkitt's lymphoma and cervical carcinoma, respectively. Both cancers shows a striking association with Epstein-Barr Virus (EBV) and human papilloma virus (HPV).T47D cell line is derived from breast cancer and is not related to certain type of virus.Objective: This study was focused on the effect of RIP from M.charantia L. on Raji, HeLa and T47D cell lines.Methods: Crude extract from M.charantia L. seeds was dissolved in 0.15 M NaCI, and then precipitated with 30-60% saturated ammonium sulphate. Precipitant was then purified with column of CM-Sepharose CL-6B with 0.5 M NaCI gradient. Cell lines grown in growth media with crude extract and active fraction of column. Lethal Doses 50% (LD50) was calculated directly for Raji cell line and used MTT for HeLa and T47D cell lines.Results: The study shows that 0.25M NaCI column fraction containing 32kDa protein had an activity on DNA supercoiled cleavage. The difference of LD50 between crude extract with 32kDa protein was not significant (p>0.05) for Raji cell line and HeLa cell line, but there was significant difference for T47D cell line. T47D cell line shows DNA fragmentation as sign of apoptosis.Conclusion: Raji cells shows more sensitive than T47D cell lines did, whereas HeLa cell line was resistant to the crude extract and 32kDa protein. In this work, the death of T47D cell line was estimated through apoptosis.Key words: column fraction - Momordica charantia L. - Raji - T47D cell lines - apoptosis.